1994
DOI: 10.1123/apaq.11.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Knowledge of Disability Throughout the Physical Education Curriculum: An Infusion Approach

Abstract: In preparing for the 21st century, faculty and professional preparation programs must be responsive to the ever-expanding knowledge base in physical education and sport, as well as the shifting economic and social conditions in society. Creative approaches to undergraduate education will be needed. Current curricular approaches in undergraduate physical education programs provide minimal preparation in disability issues for undergraduate students. Since the 1970s, specialists in adapted physical education have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…That is, PETE students are typically exposed to only one introductory-level APE course (Hodge & Jansma, 1999;Jansma, 1988;Rizzo & Kirkendall, 1995), with some programs not offering any type of practicum training (Hodge & Jansma, 1998. Such limited professional preparation has been questioned and judged inadequate in terms of preparing PETE students to teach or work effectively in inclusive physical activity settings (DePauw & Goc Karp, 1994;Kowalski & Rizzo, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, PETE students are typically exposed to only one introductory-level APE course (Hodge & Jansma, 1999;Jansma, 1988;Rizzo & Kirkendall, 1995), with some programs not offering any type of practicum training (Hodge & Jansma, 1998. Such limited professional preparation has been questioned and judged inadequate in terms of preparing PETE students to teach or work effectively in inclusive physical activity settings (DePauw & Goc Karp, 1994;Kowalski & Rizzo, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to suggest that if the quality or quantity of professional preparation (i.e., only one APE course) is limited and does not provide for adequate attitude-change strategies, PETE students' attitudes and perceived competence in teaching students with disabilities will not change favorably or may be adversely impacted. Increasingly, therefore, educators have called for restructuring of PETE programs toward an infusion curricular approach that provides information and experiences for PETE students to practice effective pedagogy with students with disabilities throughout their professional preparation (DePauw & Goc Karp, 1994;Kowalski, 1995;Kowalski & Rizzo, 1996;Sherrill & Buswell, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Institutions of higher education must take the lead to insure that future generations of KPE specialists are able to afford individuals with disabilities opportunities for culturally appropriate and normally expected physical activity experiences. Yet, KPE faculty have been slow to modify and expand course content to recognize new demands placed on individuals preparing to become teachers of regular education in public schools (DePauw & Goc Karp, 1994a, 1994b. Indeed, for the most part, university instructors have little knowledge of adapted physical activity or experience working with individuals with disabilities.…”
Section: Mandates For Changementioning
confidence: 98%
“…The third premise focuses on critical reflection by university students. As our students learn to individualize activity programs through guided hands-on experiences, they also have opportunities for systematic critical reflection, behavior analysis, and investigation of assumptions related to working with individuals with disabilities (DePauw & Goc Karp, 1994a, 1994b. If attitudes and behavior are to remain favorable, and content learned is to become permanent, KPE students must move from passive receivers of knowledge to ones who apply knowledge and reflect upon it (Boyer, 1990;Zeichner & Liston, 1987).…”
Section: Underlying Premises Of Infusion-based Curriculamentioning
confidence: 98%
“…The infusion approach curriculum means infusing disability concepts into the overall PETE curriculum; this means that teaching and training programs like PETE and APE no longer provide a segregated curriculum (Kowalski, 1995). Studies revealed that an infusion approach curriculum model could positively affect students' attitudes toward individuals with disabilities (Barrette, Holland Fiorentino, & Kowalski, 1993;DePauw &Goc Karp, 1994;Hardin, 2005;Lepore & Kowalski, 1992). There is evidence that the infusion approach curriculum positively correlates with attitudes and beliefs of pre-service teachers.…”
Section: Introductionmentioning
confidence: 99%